Hydrophilic and Hydrophobic Nanostructured Copper Surfaces for Efficient Pool Boiling Heat Transfer with Water, Water/Butanol Mixtures and Novec 649 - Matic Može; Viktor Vajc; Matevž Zupančič; Iztok Golobič (Nanomaterials, 2021)
Increasing heat dissipation requirements of small and miniature devices demands advanced cooling methods, such as application of immersion cooling via boiling heat transfer. In this study, functionalized copper surfaces for enhanced heat transfer are developed and evaluated. Samples are functionalized using a chemical oxidation treatment with subsequent hydrophobization of selected surfaces with a fluorinated silane. Pool boiling tests with water, water/1-butanol mixture with self-rewetting properties and a novel dielectric fluid with low GWP (Novec™ 649) are conducted to evaluate the boiling performance of individual surfaces. The results show that hydrophobized functionalized surfaces covered by microcavities with diameters between 40 nm and 2 µm exhibit increased heat transfer coefficient (HTC; enhancements up to 120%) and critical heat flux (CHF; enhancements up to 64%) values in comparison with the untreated reference surface, complemented by favorable fabrication repeatability. Positive surface stability is observed in contact with water, while both the self-rewetting fluids and Novec™ 649 gradually degrade the boiling performance and in some cases also the surface itself. The use of water/1-butanol mixtures in particular results in surface chemistry and morphology changes, as observed using SEM imaging and Raman spectroscopy. This seems to be neglected in the available literature and should be focused on in further studies.